2014
DOI: 10.1111/aogs.12482
|View full text |Cite
|
Sign up to set email alerts
|

Does screening for Down's syndrome cause anxiety in pregnant women? A systematic review

Abstract: Studies using quantitative, validated measures to estimate anxiety showed no association between screening and residual anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…Literature shows that having a high risk for aneuploidy significantly increases anxiousness in women (Lou et al 2015), and this was also observed in the women participating in our study. After women received a normal NIPT result there was a significant reduction in anxiety to levels considered normal (Bekker et al, 2003; Green et al 2004), although for 3% anxiety levels remained high.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Literature shows that having a high risk for aneuploidy significantly increases anxiousness in women (Lou et al 2015), and this was also observed in the women participating in our study. After women received a normal NIPT result there was a significant reduction in anxiety to levels considered normal (Bekker et al, 2003; Green et al 2004), although for 3% anxiety levels remained high.…”
Section: Discussionsupporting
confidence: 86%
“…The mere fact of having a prenatal test for fetal abnormalities may affect maternal anxiety (Nakic Rados et al 2013). Experienced levels of anxiety further increase upon receiving a high-risk result (Lou et al 2015). Anxiety is inversely correlated with, amongst others, socio-economic status (Faisal-Cury et al 2007), but might be contained by promoting informed choice for testing (Michie et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative studies have found a significant increase in anxiety following a positive screening result [2], and qualitative studies have investigated the complex information and burdensome decision-making that high-risk women face [35]. Invasive diagnostics (chorionic villus sampling (CVS) or amniocentesis) will provide a definite answer, but carry a small procedure-related risk of miscarriage.…”
Section: Introductionmentioning
confidence: 99%
“…The decision about whether or not to take the prenatal test for Down syndrome (DS) is a difficult one [1, 2]. Future parents have to decide in a context of uncertainty where results cannot be predicted or guaranteed [3–5].…”
Section: Introductionmentioning
confidence: 99%